The difference of dental anxiety in children based on frequency of dental appointment - Mia Giri Astri; Eka Chemiawan; Eriska Rriyanti (Dental Journal (Majalah Kedokteran Gigi), 2011)
Background: Problem of children’s anxiety during dental procedures is a common phenomenon. This is called dental anxiety. The anxiety children patien need to be paid a special attention, because it will affect the success of dental treatment. Purpose: The purpose of this research was to find out the difference of dental anxiety degree in children aged 8 to 12 years old based on the frequency of dental visits in dental community health centre Bandung. Methods: The method of this research was analytical descriptive. The samples collected by using purposive sampling and the amount of sample was taken by consecutive sampling, and analysed by the U Mann-Whitney test. Results: The result of this research was from 76 correspondence there was 12 children feel anxious and 64 children did not feel anxious. Asymp.Sig is less than 0.05 in children having frequent and rarely frequency of dental appointment and Asymp. Sig is more than 0.05 in children having frequent and normal frequency of dental appointment also in children having normal and rarely frequency of dental appointment. Conclusion: In conclusion, the frequency of dental visits showed the difference of children’s dental anxiety.Latar belakang: Masalah kecemasan anak saat dilakukan perawatan gigi merupakan fenomena yang sering terjadi. Kecemasan  pada saat dilakukan perawatan gigi disebut juga dental anxiety. Kecemasan pada penderita anak-anak perlu perhatian khusus karena akan memengaruhi keberhasilan perawatan gigi. Tujuan: Tujuan penelitian ini untuk mengetahui perbedaan derajat dental anxiety anak usia 8–12 tahun berdasarkan frekuensi kunjungan ke dokter gigi di Balai Pengobatan Gigi Kota Bandung. Metode: Jenis penelitian adalah deskriptif analitik. Naracoba diambil dengan metode purposive sampling dan jumlah naracoba ditentukan melalui consecutive sampling, kemudian diuji dengan U Mann-Whitney. Hasil: Hasil penelitian ini adalah dari 76 naracoba terdapat 12 anak yang merasa cemas dan 64 anak merasa tidak cemas. Asymp.Sig kurang dari 0,05 untuk perbandingan antara anak dengan frekuensi sering dan jarang berkunjung ke dokter gigi serta Asymp.Sig lebih dari 0,05 untuk perbandingan anak dengan frekuensi normal dan sering ke dokter gigi juga untuk anak dengan frekuensi normal dan jarang ke dokter gigi. Kesimpulan: Disimpulkan bahwa jumlah kunjungan ke dokter gigi memberikan perbedaan pada dental anxiety anak.